Distance Education: A Challenge for Higher Education in Indonesia - M. Rosul Asmawi (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
The implementation of educational program for all through distance learning is expected to match with the condition of Indonesia’s geography, demography, and culture that vary from one place to another. In terms of the implementation of the nine-year basic education compulsion program, Indonesia has carried out various programs, such as Package A (equal to elementary school) and Package B (equal to open junior high school) programs in many parts of provinces in Indonesia. This ‘open junior high school’ model has even been adopted as ‘open Islamic junior high school’ in other provinces. At the level of tertiary education, there is open university, as stated in the Act on National Education System No. 20 of 2003